METHODS FOR INCREASING STUDENTS' INTEREST IN LEARNING THE RUSSIAN LANGUAGE AT UNIVERSITY (Journal of Science-Innovative Research in Uzbekistan, 2024)
This paper explores various methods for increasing students' interest in learning the Russian language at university. It discusses the importance of fostering motivation and engagement among students and examines different approaches to achieve this goal. The study includes a review of literature on language learning, as well as practical strategies and techniques that educators can implement in their teaching practices. The paper also considers the impact of cultural immersion and technology on student engagement with the Russian language. By addressing these aspects, this research aims to provide valuable insights into effective methods for enhancing students' interest in learning Russian at the university level